Issues and Potentials of Research Topics in Medicines:A Research Priority Setting (RPS) in The Indonesian Institute of Sciences (LIPI) - Hadi Kardoyo; Mia Rahma Romadona; Setiowiji Handoyo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2020)
This article ilustrates the findings of research priority setting (RPS) in the field of medicine and health at the Indonesian Institute of Sciences (LIPI) in 2017. This RPS has been conducted to address issues and explore potential research topics in LIPI in the area of drug and health industry. The RPS stage has been conducted with the Delphi Method and produced five major issues, namely 1). Structure of the pharmaceutical industry in Indonesia, 2). The Role government R&D institutions and universities in the structure of the pharmaceutical industry, 3). Standardization and product supervision, and 5). Policies in the sectoral innovation system. Based on these major issues, LIPI has potential research topics that need to be developed, as follows: 1) Research on